إشكاليات تعلم النحو لدى تلاميذ السنة الخامسة إبتدائي بولاية الوادي دراسة تحليلية تقويمية في البرامج والطرائق - جنيدي, قعيد, سعاد دلال (University of El-oued, 2021)
في نهاية مطاف مذكرتنا الموسومة تحت عنوان "إشكالية تعلم النحو لدى تلاميذ السنة الخامسة إبتدائي بولاية الوادي" كان المخلص الشامل لما تناولناه خلال هذه الدراسة كالتالي: الفصل الأول كان انطلاقة تعريفات للنحو من كلا الجانبين اللغوي والاصطلاحي والتي تمحورت حول أن النحو وسيلة لضبط اللسان من اللحن والخطأ وتطرقنا إلى أنواع النحو التي كانت على شاكلتين التعليمي والتخصصي ثم تطرقنا إلى وظيفة النحو والتي تمثلت في الإعراب وتقويم اللسان وإلى منطلقات تدريس النحو وأهدافه المهمة وخصائصه وطرائق تدريسه ثم صعوباته كمادة علمية والصعوبات التي تقف عائقا أمام تعلمه، وبما أن لكل مشكلة حل تطرقنا إلى الوسائل المساعدة لتسهيل تعليم القواعد النحوية. وكان الفصل الثاني تحليلا للدراسة الميدانية التي أجريت في مدارس الوادي وتحليل إجابات الأساتذة وتمثيل نسبة الإجابات في دوائر نسبية. ثم كان الفصل الثالث كدراسة لمعوقات النحو وسبل تذليلها، حيث درسنا فيه العوامل الثلاث المتآزرة في صعوبة النحو لدى التلاميذ (المعلم، المتعلم، المنهاج) وأرفقت هذه الأخيرة بمجموعة حلول من طرف أساتذة المادة ومن طرفنا للتقليل من هذا الحاجز. وبهذا رست سفينة بحثنا على شواطئ الختام لترسى على مرسى الخاتمة التي كانت عبارة عن نتائج عامة وخاصة لما استنتجناه خلال هذه الدراسة وأرفقت كذلك بحلول وتوصيات هامة لتجنب الحواجز التي تقف كعائق أمام تعلم النحو لتلاميذ السنة الخامسة من التعليم الإبتدائي. At the end of our memo, tagged under the title "The problem of learning grammar among students of the fifth primary year in the state of the valley", the comprehensive summary of what we discussed during this study was as follows: The first chapter was the launch of definitions of grammar from both the linguistic and idiomatic sides, which revolved around the fact that grammar is a means of controlling the tongue from melody and error. And the methods of teaching it, then its difficulties as a scientific subject, and the difficulties that stand in the way of learning it, and since every problem has a solution, we touched on the aids to facilitate the teaching of grammatical rules. The second chapter was an analysis of the field study conducted in the valley schools, an analysis of the teachers' answers, and a representation of the percentage of answers in relative circles. Then the third chapter was a study of grammar obstacles and ways to overcome them, in which we studied the three synergistic factors in the difficulty of grammar for students (teacher, learner, curriculum) and the latter was attached to a set of solutions from the professors of the subject and from us to reduce this barrier. Thus, our research ship docked on the shores of the conclusion to dock on the berth of the conclusion, which were general and specific results of what we concluded during this study and were also attached to important solutions and recommendations to avoid the barriers that stand as an obstacle to learning grammar for students of the fifth year of primary education
Keywords: : Problems, learning grammar, students, programs, methods; إشكاليات، تعلم النحو، تلاميذ، البرامج، الطرائق